2012
DOI: 10.4315/0362-028x.jfp-12-115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characteristics of Vibrio spp. Isolated from Preharvest Shrimp of the North Western Province of Sri Lanka

Abstract: This study investigated the prevalence and molecular characteristics of Vibrio spp. in farmed shrimp (Penaeus monodon) in Sri Lanka. A total of 170 shrimp samples (100 g of whole shrimp each) taken from individual ponds from 54 farms were collected 1 week prior to harvest from the North Western Province of Sri Lanka. Overall, 98.1% of the farms and 95.1% of the ponds were positive for Vibrio spp. in shrimp; at the pond level, V. parahaemolyticus (91.2%) was most common, followed by V. alginolyticus (18.8%), V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…The results of this study are supported by previous research results, Koralage et al (2012) and Traoré et al (2014) Sumatera and Muara Angke, North Jakarta. Blake et al (1980), Hill et al (2011), and Khariri (2012) found a match between V. cholerae derived from the environment such as seafood and drinking water sources with V. cholerae outbreaks.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are supported by previous research results, Koralage et al (2012) and Traoré et al (2014) Sumatera and Muara Angke, North Jakarta. Blake et al (1980), Hill et al (2011), and Khariri (2012) found a match between V. cholerae derived from the environment such as seafood and drinking water sources with V. cholerae outbreaks.…”
Section: Discussionsupporting
confidence: 91%
“…The strain set consisted of four groups based on the geographic origin of strains and the sampling events: the first group was obtained from prawn farms located in three Sri Lankan regions (n = 43) [30], the second group consists of strains (n = 34) that were isolated from regional and imported food samples in Germany (at retail) of different geographic origins and sample types. Within the third group 27 isolates obtained from local markets and prawn farms in Ecuador are grouped.…”
Section: Methodsmentioning
confidence: 99%
“…In rare cases, V. parahaemolyticus infection can be fatal [2]. This pathogen is disseminated worldwide and is considered a leading cause of seafood-borne illness in several Asian countries [3,4] and in the United States [5]. For this reason, it is important to understand its many virulence factors and their effects on the human host.…”
Section: Introductionmentioning
confidence: 98%